Implementation of Tools for Lessening the Influence of Artifacts in EEG Signal Analysis. - Molina-Molina, Mario; Tardón-García, Lorenzo José; Barbancho-Pérez, Ana María; Barbancho-Pérez, Isabel (MDPI, 2024)
This manuscript describes an implementation of scripts of code aimed at reducing the influence of artifacts, specifically focused on ocular artifacts, in the measurement and processing of electroencephalogram (EEG) signals. This process is of importance because it benefits the analysis and study of long trial samples when the appearance of ocular artifacts cannot be avoided by simply discarding trials. The implementations provided to the reader illustrate, with slight modifications, previously proposed methods aimed at the partial or complete elimination of EEG channels or components obtained after independent component analysis (ICA) of EEG signals. These channels or components are those that resemble the electro-oculogram (EOG) signals in which artifacts are detected. In addition to the description of each of the provided functions, examples of utilization and illustrative figures will be included to show the expected results and processing pipeline.
Keywords: Procesado de señales; Electroencefalografía; Electrodiagnóstico - Proceso de datos; EEG signal pre-processing; Matlab–Fieldtrip; Artifacts; Independent component analysis